2023
DOI: 10.3390/molecules28207033
|View full text |Cite
|
Sign up to set email alerts
|

Mucin Glycans: A Target for Cancer Therapy

Lingbo Sun,
Yuhan Zhang,
Wenyan Li
et al.

Abstract: Mucin glycans are an important component of the mucus barrier and a vital defence against physical and chemical damage as well as pathogens. There are 20 mucins in the human body, which can be classified into secreted mucins and transmembrane mucins according to their distributions. The major difference between them is that secreted mucins do not have transmembrane structural domains, and the expression of each mucin is organ and cell-specific. Under physiological conditions, mucin glycans are involved in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 200 publications
0
6
0
Order By: Relevance
“…Alterations in the glycosylation of proteins outside the immune system can lead to those proteins becoming pro-transforming agents. The most well documented example to date is the MUC1 protein, which normally functions, when properly glycosylated, as a coactivator of transcriptional elements related to metabolic functions [ 23 ]. MUC1 overexpression has been found in many types of cancer [ 23 ], and is certainly found in bladder cancer [ 24 ].…”
Section: Glycosylation and Bladder Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations in the glycosylation of proteins outside the immune system can lead to those proteins becoming pro-transforming agents. The most well documented example to date is the MUC1 protein, which normally functions, when properly glycosylated, as a coactivator of transcriptional elements related to metabolic functions [ 23 ]. MUC1 overexpression has been found in many types of cancer [ 23 ], and is certainly found in bladder cancer [ 24 ].…”
Section: Glycosylation and Bladder Cancermentioning
confidence: 99%
“…The most well documented example to date is the MUC1 protein, which normally functions, when properly glycosylated, as a coactivator of transcriptional elements related to metabolic functions [ 23 ]. MUC1 overexpression has been found in many types of cancer [ 23 ], and is certainly found in bladder cancer [ 24 ]. Expression analysis has revealed that MUC1 expression is significantly increased in bladder tumor tissues, as well as lymphatic metastases [ 25 ].…”
Section: Glycosylation and Bladder Cancermentioning
confidence: 99%
“…O-linked glycosylation often occurs in the Golgi and Endoplasmic Reticulum [6]. O-glycans are generated by adding Nacetylgalactosamine (GalNAc), N-acetylglucosamine, fucose, glucose, xylose, mannose, or galactose to serine (Ser) and threonine (Thr) residues of proteins [7]. O-GalNAc glycosylation (Mucin-type Oglycosylation) is initiated by a family of 20 homologous genes encoding polypeptide GalNActransferases (ppGALNTs), and the enzymatic process is initiated in in the Golgi [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…The expression of each mucin is organ- and cell-specific. Alterations in mucin expression, glycosylation, or localization have been seen in a variety of pathological conditions, such as cancers, inflammatory bowel disease, and ocular disease (see review articles 1 3 ).…”
mentioning
confidence: 99%
“…Collectively, these mucins contribute to regulating the host-environment interactions at mucosal surfaces through various mechanisms ranging from forming physiochemical barriers to regulating signal transduction pathways in epithelial. 1 4 …”
mentioning
confidence: 99%